Robert Kilwardby's science of logic : a thirteenth-century intensional logic - Thom, Paul (Investigating medieval philosophy, 2019)
Paul Thom's book presents Kilwardby's science of logic as a body of demonstrative knowledge about inferences and their validity, about the semantics of non-modal and modal propositions, and about the logic of genus and species. This science is thoroughly intensional. It grounds the logic of inference on that in virtue of which the inference holds. It bases the truth conditions of propositions on relations between conceptual entities. It explains the logic of genus and species through the notion of essence. Thom interprets this science as a formal logic of intensions with its own proof theory and semantics. This comprehensive reconstruction of Kilwardby's logic shows the medieval master to be one of the most interesting logicians of the thirteenth century.